Which defensive tactical indicators are associated with victory in the semifinals and finals of the 2014 FIFA World Cup? - Leonardo Panice (Motriz: Revista de Educacao Fisica, 2020)
Abstract Aim: The objective of this study was to verify whether the match winners in the semifinals and finals of the FIFA World Cup 2014 were those who presented the highest frequency of pressing and intense behaviors in the recovery of ball possession. Methods: The sample was composed of 533 defensive tactical sequences performed by the four finalist teams in the 2014 FIFA World Cup. The independent t-test was used to compare tactical indicators between winning and losing teams and the chi-square test (X2) was applied to assess the association between the variables. Results: In the first (X2 = 48.47; P < 0.01) and second halves of regular matches (X2 = 64.10; P < 0.01), the evaluated teams recovered the ball in the defensive zone. However, during the first and second periods of extra time, the highest frequencies of ball recovery were found in the middle defensive zone (P < 0.01). Conclusion: It is concluded that the semi-finalist and finalist teams from the 2014 FIFA World Cup sought to recover the ball in the defensive zone, and pressing opponent movements when they were losing the matches.